PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIIIA SMP NEGERI 1 ROKAN IV KOTO - Sartika Ardina; Atma Murni; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is based on mathematics learning achievement on Matrix topic of students XI IPS 1 MAN Insan Cendekia Siak which shows that 12 of 23 students still have scores which stand under Minimum Mastery Criteria (MMC) that has been settled by the school that is 76. This research aims to improve learning process and students’ mathematics learning achievement by applying Discovery Learning (DL) model. The type of this research is classroom action research with two cycles. The research instruments used are mathematical learning instruments and data collecting instruments. The mathematical learning instruments are syllabus, lesson plans, and students worksheet. The data collecting instruments are observation sheets and students mathematic tests. Analysis techniques that used are descriptive narrative on qualitative data and descriptive statistics on quantitative data. Subject of this research are students of XI IPS 1 MAN Insan Cendekia Siak in first semester of academic year 2018/2019, which consist of 9 males and 14 females with heterogeneous abilities. Based on the analysis of students and teacher activities after implementation of the DL model, it can be concluded that there is an improvement of learning process. On knowledge competence, in first cycle with percentage 87% and 96% in second cycle. On skill competence, the number of students who can reach MMC in first cycle with percentage 78,3% and 82,6% in second cycle. Based on the result, it can be concluded that the implementation of DL model can improve the learning process and the students’ mathematics learning outcomes at class XI IPS 1 MAN Insan Cendekia Siak .Key Words: Mathematics Learning Achievement, Discovery Learning Model,Classroom Action Research